Conjunctive Query Inseparability of OWL 2 QL TBoxes - Konev, Boris; Kontchakov, Roman; Ludwig, Michel; Schneider, Thomas; Wolter, Frank; Zakharyaschev, Michael (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
The OWL 2 profile OWL 2 QL, based on the DL-Lite family of description logics, is emerging as a major language for developing new ontologies and approximating the existing ones. Its main application is ontology-based data access, where ontologies are used to provide background knowledge for answering queries over data. We investigate the corresponding notion of query inseparability (or equivalence) for OWL 2 QL ontologies and show that deciding query inseparability is PSPACE-hard and in EXPTIME. We give polynomial time (incomplete) algorithms and demonstrate by experiments that they can be used for practical module extraction.